Paleogene depositional environments of the Frysjaodden and Hollendardalen formations in central Spitsbergen - Burca, Florin (2008)
ABSTRACT The current study reveals the transgressive-regressive sequences and depositional environments of Paleogene Frysjaodden and Hollendardalen formations recorded in the Central Tertiary Basin of Spitsbergen. In addition, the most rapid and significant climatic perturbation of the Cenozoic era, known as PETM (Paleocene-Eocene Thermal Maximum) is discussed using mineralogical data. The paleoenvironment has been reconstructed using a combination of sedimentary field data, XRD, micropaleontology and detailed analyses of clay minerals. The results display a shallowing upward succession developing from offshore shales into a distinct offshore-transition zone with storm-generated sand beds including hummocky cross stratification and fragments of fossil wood. The succeeding sediments reveal shoreface and foreshore deposits characterized by low angle cross stratified sandstones. The upper most part of the section is interpreted as beach-ridge strandplains with coal seams and roots structures in an inferred lagoonal or marsh setting. Key words: lithofacies, sedimentology, Paleogene, PETM, Svalbard, XRD, thin sections, clay minerals